Existence of Solutions of a Viscoelastic p(x)-Laplacian Equation with Logarithmic Nonlinearity - Narayanan, Lakshmipriya; Soundararajan, Gnanavel (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we aim to obtain the existence of weak solutions of a p(x) -Laplacian pseudo-parabolic equation with memory term and logarithmic nonlinearity. Moreover, a lower bound for blow up time is also established using the differential inequality technique when the solution blows up at a finite time T^.